An investigation of motivations of Consumer participation in co-creation activities through communities: A case study of the fashion industry - Guan, Guixin (2014)
Purpose of study The purpose of the study is to explore and describe consumer motivation to participate in co-creation activities through online and offline communities. The fast development of technology has infused into fashion industry and increases the use of online fashion communities as a means to engage consumers. The haul caused by technology reduces the focus on offline fashion community for research. However, believing that both kinds of communities have its value, it is important to take into account both community contexts for study. Furthermore, to optimize value co-creation through communities, it is critical to understand consumer motivation behind this behaviour.